Islamic Legal Analysis on the Protection of Vulnerable Age Groups from Online Gender-Based Violence (OGBV) in Indonesia - Khotimah, Umi Khusnul (Journal of Ecohumanism, 2024)
Gender-Based Online Violence (GBOV) poses a significant challenge in safeguarding vulnerable groups, particularly in Indonesia, where digital literacy remains low among women and children. This study aims to analyze the phenomenon using the framework of Maqashid Syariah, emphasizing the protection of life (hifz an-nafs), dignity (hifz al-’ird), and progeny (hifz an-nasl). Employing a qualitative method, data were collected through literature reviews, case studies, and expert interviews to examine the intersection of Islamic principles and national legal frameworks, such as the Information and Electronic Transactions Law (ITE Law) and the Law on Sexual Violence Prevention (TPKS Law). The findings highlight that while Islamic principles provide a robust moral and legal foundation to combat GBOV, the implementation of national regulations remains inadequate due to gaps in specificity and enforcement. Additionally, the lack of digital literacy among vulnerable populations exacerbates the risks. This study underscores the importance of integrating Maqashid Syariah into policymaking, enhancing digital literacy through Islamic ethics, and fostering collaboration between government, religious leaders, and communities. These measures aim to create a safer, more inclusive digital environment while addressing GBOV comprehensively. The research offers a novel perspective by aligning Islamic jurisprudence with modern policy needs, contributing to the discourse on ethics and law in the digital age.